Interrelation of Islamic Formal and Islamic Principles in The Context of The Country’s Constitution (The Application of Islamic Law for Corruptors in Indonesia) - Imam Syafi’i; Subairi (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2020)
Corruption has made the life of the state have porous joints. Economy as the mainstay of the joint life experience fragility, currency values decline significantly. Social joints also suffer the same fate, now corruption has become commonplace in everyday life portrait began to level the structure of RT (Neighborhood) up to the level of institution of the President. In fact, even this body of organisms may have been "plagued" the virus of corruption that is far more devastating impact than physical disease viruses. Many people suspect that corruption in Indonesia is still running and even increased in almost every element of the institution due to the form of sanctions contained in the positive law. Where sanctions are used as a "cure" the disease is not effective or have no impact on the offender and not relevant to apply again. From the above problem, the author wishes to conduct research regarding the form of criminal sanctions for corruption in Indonesia using qualitative approaches that are library research (literature study), and data collection techniques using documentary study of the books, scientific works, newspapers, magazines, and scholarly journals. After doing research, followed by analyzing each of the data obtained, the researchers found a conclusion that could answer the focal issues under review, islamic law view that corruption is a criminal sanction ta'zir, where the imposition of sanctions tailored to the level of crimes committed, sikologis actors and their environment, with the shape and type of sanctions that may deter perpetrators and educate the offender and other people not to commit criminal them. And including sanctions model in Islamic law is a prison and a fine. The rules contained in Islam and the state (positive law) have the same goal, namely to create peace between humans. For this reason, positive criminal law must not conflict with Islamic law. Although the regulations stipulated in Indonesia are not taken from the texts of the al-Qur`an or al-Hadith. But still in line with the basic principles set out in Islamic law. Abstrak Korupsi telah membuat sendi kehidupan bernegara mengalami kekeroposan. Sendi perekonomian sebagai penopang utama kehidupan mengalami kerapuhan, nilai mata uang secara signifikan mengalami kemerosotan. Sendi sosial juga bernasib sama, saat ini korupsi telah menjadi hal lumrah dalam potret kehidupan keseharian mulai tingkat struktur RT (Rukun Tetangga) hingga ke tingkat Lembaga Kepresidenan. Bahkan organisme tubuh inipun mungkin telah “dijangkiti” virus korupsi yang jauh lebih dahsyat dampaknya dari virus-virus penyakit jasmani. Banyak kalangan menduga, korupsi di Indonesia tetap berjalan dan bahkan meningkat hampir di setiap elemen lembaga dikarenakan bentuk sanksi yang terdapat dalam hukum positif. Dimana sanksi yang dijadikan "obat" terhadap penyakit tersebut tidak efektif atau tidak berdampak apapun terhadap pelaku dan tidak relevan untuk diterapkan lagi. Dari masalah diatas, penulis berkeinginan untuk melakukan penelitian tentang bentuk sanksi pidana korupsi di Indonesia dengan menggunakan pendekatan kualitatif yang bersifat library research (penelitian kepustakaan), dan tehnik pengumpulan datanya menggunakan telaah dokumenter terhadap kitab-kitab, karya ilmiah, surat kabar, majalah, dan jurnal keilmuan. Setelah melakukan penelitian yang dilanjutkan dengan menganalisa setiap data yang diperoleh, peneliti menemukan kesimpulan, Hukum islam memandang bahwa Sanksi tindak kriminal korupsi adalah ta'zir, dimana pemberian sanksi disesuaikan terhadap tingkat kriminal yang dilakukan, sikologis pelaku dan lingkungannya, dengan bentuk dan jenis sanksi yang dapat menjerakan pelaku dan mendidik pelaku serta masyarakat lain untuk tidak melakukan kriminal tersebut. Dan termasuk model sanksi dalam hukum islam adalah penjara dan denda. Aturan-aturan yang terdapat dalam islam dan negara (hukum positif) adalah memiliki tujuan yang sama, yaitu untuk menciptakan kedamaian antar umat manusia. Untuk itulah hukum pidana positif harus tidak bertentangan dengan hukum islam. Walau peraturan-peraturan yang ditetapkan di indonesia tidak diambil dari nash-nash al-Qur`an maupun al-Hadits. Tetapi tetap selaras dengan prinsip dasar yang ditetapkan dalam hukum islam.